2009
DOI: 10.1534/genetics.109.108654
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Multiple UNC-40 (DCC) Receptor-Mediated Signals in Determining Neuronal Asymmetry Induced by the UNC-6 (Netrin) Ligand

Abstract: The polarization of post-mitotic neurons is poorly understood. Preexisting spatially asymmetric cues, distributed within the neuron or as extracellular gradients, could be required for neurons to polarize. Alternatively, neurons might have the intrinsic ability to polarize without any preestablished asymmetric cues. In Caenorhabditis elegans, the UNC-40 (DCC) receptor mediates responses to the extracellular UNC-6 (netrin) guidance cue. For the HSN neuron, an UNC-6 ventral-dorsal gradient asymmetrically localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(55 citation statements)
references
References 27 publications
7
48
0
Order By: Relevance
“…7G). These results are consistent with previous results showing that UNC-6 localizes UNC-40 to the ventral surface of the HSN and, in an unc-6 mutant, UNC-40 localizes uniformly around the cell body and protrusions extend from around the cell body (Xu et al, 2009). These results indicate that UNC-5, UNC-6 and UNC-40 control the polarity of filopodial protrusion from growth cones that are repelled (VDs) or attracted (HSNs) to UNC-6/netrin.…”
Section: Unc-5 Unc-6 and Unc-40 Affect Polarity Of Growth Cone Filopsupporting
confidence: 93%
See 1 more Smart Citation
“…7G). These results are consistent with previous results showing that UNC-6 localizes UNC-40 to the ventral surface of the HSN and, in an unc-6 mutant, UNC-40 localizes uniformly around the cell body and protrusions extend from around the cell body (Xu et al, 2009). These results indicate that UNC-5, UNC-6 and UNC-40 control the polarity of filopodial protrusion from growth cones that are repelled (VDs) or attracted (HSNs) to UNC-6/netrin.…”
Section: Unc-5 Unc-6 and Unc-40 Affect Polarity Of Growth Cone Filopsupporting
confidence: 93%
“…We next determined whether orientation of filopodial protrusion was altered in unc-5, unc-6 and unc-40 mutants. Previous studies indicated that UNC-6 was required for polarized distribution of UNC-40 and MIG-10/lamellipodin on the ventral region of the HSN neuron and that unc-6 and unc-40 mutant HSN neurons displayed a loss of polarized ventral protrusion (Adler et al, 2006;Quinn et al, 2006;Xu et al, 2009). To quantify polarity of filopodial protrusion, we divided the growth cones into four quadrants along the AP and DV axes, based upon the orientation of the animal, regardless of the direction that the growth cone was navigating (some VD growth cones in mutants were misguided and were migrating laterally or even ventrally; and many HSN growth cones protruded laterally rather than ventrally).…”
Section: Unc-5 Unc-6 and Unc-40 Affect Polarity Of Growth Cone Filopmentioning
confidence: 99%
“…This model was proposed from genetic evidence that indicates that conformational changes to the UNC-40 receptor can trigger independent signals (Xu et al 2009). One signal causes the UNC-40 receptor to polarize to one side of the neuron, whereas another acts to orient the localization relative to the gradient of the UNC-6 ligand.…”
Section: Models Of Axon Guidancementioning
confidence: 99%
“…UNC-40 self-organizing polarization is a stochastic process (Xu et al 2009;Kulkarni et al 2013). The UNC-40 receptor will asymmetrically localize to one surface with some probability.…”
Section: Models Of Axon Guidancementioning
confidence: 99%
See 1 more Smart Citation